Pathomorphological Alterations of Aggressive Genital and Extra-genital Canine Transmissible Venereal Tumour - Kumar, Amit; Syal, Priyanka; Singh, Inder Pal; Bhardwaz, Anavil; Kumar, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Transmissible venereal tumor (TVT) is one of the most common tumors in canines that mainly spread via mating. These tumors grow on the external genitalia and appear like cauliflower growth which can be nodular, papillary, pedunculated, or multilobulated and may cause serosanguinous discharge or bleeding from preputial orifices and genital canal in males and females, respectively (Panchkhande et al., 2019). It is also referred as venereal granuloma, canine transmissible venereal sarcoma, transmissible lymphosarcoma, and sticker tumor of mesenchymal origin (Saravanan et al., 2015).